Effect of thermosonication on pectin methylesterase activity and quality characteristics of orange juice - Lorencini Schuina, Guilherme (Revista Ciência Agronômica, 2021)
Pectin methylesterase (PME) is the enzyme responsible for quality losses in orange juice and pasteurization is used to inactivate PME. This process decreases the sensory and nutritional aspects of the beverage. This study aimed to evaluate the effect of combined ultrasound and moderate temperature on several quality parameters of orange juice, and whether the used treatment resulted in a reduction of PME activity when compared to thermally treated samples and natural juice. Thermosonication is an alternative preservation method that allows a signifi cant decrease in PME activity and a smaller loss of vitamin C. The treatment with 40 kHz ultrasound and a temperature of 60 °C resulted in the highest reduction of PME activity. For ascorbic acid, the lower the heat used in combination with sonication, the smaller the loss of this compound. Soluble solids content, pH, and color of the juice did not alter during processing.